Management Challenges of Chronic Suppurative Otitis Media in Sub-Saharan Africa: A Call for Urgent Action - Adedeji, T O; Tobih, J E; Adegbosin, B A (West African journal of medicine, 2025)
Chronic suppurative otitis media is a serious health care concern in sub-Saharan Africa. Poverty, ignorance, and non-availability of surgical treatment techniques militate against its effective management. A retrospective descriptive study conducted at UNIOSUN Teaching Hospital, Osogbo on patients with CSOM over five years. A total of 428 patients consisting of 232 males and 196 females with age ranged from 1 - 83 years. Children 1-15 years constituted the largest (54.2%) proportion. RCSOM (37.4%), LCSOM (29.9%) and bilateral CSOM (32.7%). Majority (51.4%) had discharge for more than 2 years. Most patients 208 (48.6%) had moderate size perforations and majority (93.5%) were central perforations. Culture results showed pseudomonas 24.3% and staphylococcus aureus 24.3% as the most common organisms isolated. PTA of 152 patients (reviewed) showed that 36.8% had moderate degree of HL and severe degree HL in 26.3%. Ninety four (61.8%) had conductive hearing loss. Hearing loss was significantly associated with the size of perforation (p = 0.001) and duration of ear discharge (p = 0.022). About 99% of patients were managed conservatively with topical ear drops/ dressing with wick gauze impregnated with ciprofloxacin ear drops. Five patients (1.17 %) had tympanoplasty, six (1.40%) had cortical mastoidectomy and 2 (0.47%) patients died secondary to intracranial complications. Challenges militating against effective management of CSOM in Nigeria include poverty, delayed presentation, few tympanomastoid surgical experts and poor attitude toward surgical procedures. Public enlightenment including early presentation of patients, provision of adequate equipment and focused attention on appropriate surgical techniques should be embarked upon urgently.